Association between sub-cortical beetles, mites, and ophiostomatoid fungi on trees in South African Afromontane forests - Musvuugwa, Tendai; Dreyer, Leanne; Roets, Francois (African Entomology, 2024)
Sub-cortical beetles and mites contribute to tree mortality by creating wounds and by spreading potential pathogens. Here we elucidate associations between sub-cortical beetles, mites, and ophiostomatoid fungi from trees in Afromontane forests in South Africa. Bark and wood samples were collected from native tree species and exotic Pinus radiata and Acacia mearnsii that showed signs of sub-cortical beetle activity, or from wounds on storm-damaged trees. Ophiostomatoid fungi, a group that contains numerous tree pathogens, were isolated from beetles that emerged from samples, their galleries, phoretic mites on these beetles, and from wounds and wound-associated mites. Fungal isolates were identified using multiple DNA markers. Twenty sub-cortical beetle, 22 mite and 16 ophiostomatoid fungal species were recovered from only a few native and exotic host tree species. Three fungal species are likely undescribed despite increased focus on this ecologically and economically important group worldwide. Significantly, some mites and fungi were isolated from native and non-native hosts. Wound-associated fungi and mites were less host-specific than sub-cortical beetle-associated taxa. We highlight the rich and still unexplored symbioses between sub-cortical beetles, mites, and ophiostomatoid fungi in Afromontane forests and provide a foundation for future studies on the ecology of these important organisms.